Determining Factors of Fe Tablet Consumption among Pregnant Women at BPM S Tangerang - Br Sembiring, Dewi Sartika; Diah Soliha (SABDA EDU PRESS (SEP), 2024)
Maternal Mortality Rate (MMR) is an indicator of the success of maternal health efforts and assesses community welfare. The sample in this study was all 56 pregnant women in the third trimester at BPM S Tangerang Banten in 2023. The data analysis used was univariate and bivariate with the chi square test. there is no significant relationship between age and consumption of Fe tablets where p value = 0.050 > α = 0.05, there is no significant relationship between education and consumption of Fe tablets where p value = 0.982 > ᾱ = 0.05. There is no significant relationship between work and tablet consumption where the p value = 0.158 > α = 0.05. There is a significant relationship between the frequency of ANC visits and the consumption of Fe tablets in pregnant women where the p value = 0.046 < α = 0.05. There is no significant relationship between gravida and the consumption of Fe tablets where the p value = 0.301 > α = 0.05.Conclusion: The factor causing the low consumption of Fe tablets is ANC visits.